Response of fennel (Foeniculum vulgare Mill.) to phosphorus and zinc fertilization in a loamy sand soil - S R Kumawat, S K Kumawat, B L Yadav, (Journal of Spices and Aromatic Crops, 2015)
The field experiment was conducted with four levels of phosphorus (0, 20, 40, and 60 kg ha-1) and four levels of ZnSO4 (0, 15, 30 and 45 kg ha-1) to study their effects on growth and yield of fennel. Application of P upto 40 kg ha-1 significantly increased days to 50% flowering, plant height, number of branches, number of umbels plant-1, number of umbellets umbel-1, seeds umbel-1, seed and stover yield, net return and B:C ratio. The delay in 50% flowering, plant height, number of branches plant-1, number of umbels plant-1, number of umbellets umbel-1 and seeds per umbel-1, seed and stover yield, net return and B:C ratio increased significantly upto 30 kg ZnSO4 ha-1. The combined application of P @ 40 kg ha-1 and Zn @ 30 kg ZnSO4 ha-1 was significantly superior with respect to umbels plant-1, seed and stover yield as compared to other combinations of P and ZnSO4. The economic optimum dose of P and ZnSO4 was computed as 53.85 kg ha-1 with response of 1245.66 kg ha-1 and 39.03 kg ha-1 with the response of 1255.94 kg ha-1, respectively.